Fusarium Stalk Rot of Maize –Impact on Maize Production - Basha, S. Ameer; Ramya, V.; Sagar, B. Vidya; Devi, G. Uma (Chronicle of Bioresource Management, 2023)
Fusarium stalk rot is one of the most devastating soil-borne diseases of maize, occurring in all continents of the world including India. Post-flowering stalk rots of maize is attacked by more than fifteen species of Fusarium. Water stress and high soil temperature at flowering are the predisposing factors for this disease at post flowering stage. In general, potassium fertilizers reduces, but, that of nitrogen if in excess, increase the severity of the stalk rot disease. In this article, the distribution, symptoms, epidemiology, disease cycle, genetics of resistance, impact of the disease and integrated disease management approaches are discussed.